Development of boric acid added pumice based insulation material - Palaci, Yuksel (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2022)
In this study, the effect of boric acid additive on the thermal conductivity and density of pumice for ceramic foam production was investigated. In addition, 20% perlite and cenosphere were added to this mixture, and its effect on thermal conductivity variation was examined. Boric acid was added to the pumice at a rate of 50% and the effect of sintering temperatures of 500, 600 and 700 degrees C on the mixture density and thermal conductivity was measured. In addition, the effect of perlite and cenosphere on the thermal conductivity of the pumice-boric acid mixture was investigated by sintering at 700 degrees C, where the lowest thermal conductivity was obtained for pumice. The increase in temperature decreased the thermal conductivity of the Pumice Boric acid mixture. The addition of boric acid to pumice, with sintering at 700 degrees C, reduced the thermal conductivity by 42%, 0.236 W/ m.K and the density by 44.8%, reduced to 0.64 g/cm3. As expected, boric acid addition lowered the melting temperature of pumice. The addition of perlite and cenosphere to the pumice-boric acid increased the thermal conductivity and density when the mixture was sintered at 700 degrees C. Perlite addition increased the thermal conductivity to 0.374 W/m.K, while the addition of cenosphere decreased to 0.359 W/m.K. While the density decreased to 1.06 g/cm3 with the addition of perlite, it decreased to 1.10 g/cm3 with the addition of cenosphere.
Keywords: Pumice; boric acid; perlite; cenosphere; thermal conductivity; Engineering